PROTOCOL ON SAFETY AT HIGH-RISK MATCHES - Krešimir Nimac; Joško Žganjer (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In the Republic of Croatia, as in most other countries, riots at sports competitions are escalating. In order to effectively apply regulations related to the prevention of riots at sports competitions, the Republic of Croatia adopted the Protocol on safety at High-Risk Matches. In this paper, the author analyzes the provisions of the Protocol as well as its effectiveness so far in preventing disorder at sport competitions.